2014
DOI: 10.1002/j.1839-4655.2014.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Toleration or trust? Investigating the acceptance of ‘boat people’ among young Australians

Abstract: There has been intense debate in Australia regarding how asylum seekers who arrive by boat should be treated. Some call for compassion towards those prepared to risk their lives to seek protection, whereas others believe 'boat people' should not be allowed into the country. This article uses data from a large representative sample of young people in Queensland, Australia, to understand the acceptance of asylum seekers by young people in Australia. The findings suggest that young Australians are more accepting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The impact of discourse on roles and relationships was also noted as significantly affecting the ability of asylum seekers and refugees to develop stability within their new community. For example, several studies noted that in some communities, particularly those faced with economic challenges, refugees and asylum seekers may be discursively represented as destitute, dependent, and demanding people, arriving to strip the community of resources and welfare (Every et al, 2013; Hightower, 2015; Laughland-Booy, Skrbis, & Tranter, 2014; Spinney & Nethery, 2013). A number of studies also found that those unaware of the circumstances of refugees and asylum seekers, questioned at times the increasing presence of these individuals in their community and what impact this may have on their own job opportunities and social cohesion (Hanson-Easey & Augoustinos, 2011; McKay, Thomas, & Kneebone, 2011; Posselt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of discourse on roles and relationships was also noted as significantly affecting the ability of asylum seekers and refugees to develop stability within their new community. For example, several studies noted that in some communities, particularly those faced with economic challenges, refugees and asylum seekers may be discursively represented as destitute, dependent, and demanding people, arriving to strip the community of resources and welfare (Every et al, 2013; Hightower, 2015; Laughland-Booy, Skrbis, & Tranter, 2014; Spinney & Nethery, 2013). A number of studies also found that those unaware of the circumstances of refugees and asylum seekers, questioned at times the increasing presence of these individuals in their community and what impact this may have on their own job opportunities and social cohesion (Hanson-Easey & Augoustinos, 2011; McKay, Thomas, & Kneebone, 2011; Posselt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Werge-Olsen and Vik (2012) suggested that the extent to which refugees and asylum seekers can realize their occupational potential is heavily influenced by the cultural norms and social attitudes to which they are exposed. In a similar vein, a number of studies argued that discursive practices that position refugees and asylum seekers as different, troublesome, threatening, or greedy, foster an unwelcoming atmosphere and compromise occupational opportunities (Edgeworth, 2015; Hightower, 2015; Laughland-Booy et al, 2014; Phillips, 2015). Two papers also noted that pursuance of a personally meaningful life in Australia requires refugees and asylum seekers to persevere and find creative solutions in negotiating where they fit and what they can contribute to Australian society (Boyle, 2014; Sulaiman-Hill & Thompson, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such recurrently distorted representations of refugees raise the question of whether this is a common journalistic tendency or inherently culturally and politically bound. Several comparative studies report that refugees’ depictions in newspapers are predominantly negative across different cultures and political systems (Bleiker et al, 2013; Greussing and Boomgaarden, 2017; Laughland-Booy et al, 2014; Parker, 2015). Exceptions to this trend have been observed by Sulaiman-Hill et al, (2011), who found that New Zealand newspapers expressed a strong humanitarian tone between 1998 and 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blinder and Allen, 2016; O’Regan and Riordan, 2018; Parker, 2015), their association with crime and deviant behavior (e.g. Vicsek et al, 2008) and their depiction as threats to national security, social cohesion, and economic stability of local communities (Bleiker et al, 2013; Elsamni, 2016; Greussing and Boomgaarden, 2017; Laughland-Booy et al, 2014; Lueck et al, 2015; Pedersen and Hartley, 2015). To a smaller extent, the humanitarian perspective on refugees in the media has been tackled by a number of studies (e.g.…”
Section: Introductionmentioning
confidence: 99%